2019
DOI: 10.1016/j.jogc.2019.08.038
|View full text |Cite
|
Sign up to set email alerts
|

From Tragedy to Triumph: Canadian Connections in the Management of Rhesus Hemolytic Disease of the Newborn

Abstract: J ohn Ballantyne (1861Ballantyne ( -1923 of Edinburgh wrote that the first record of fetal hydrops was given by Hippocrates in The Epidemics with a description of a "fleshy foetus" with "general foetal dropsy." 1 It is probable that the French midwife, Louise Bourgeois (1563-1636), gave the first account of hemolytic disease of the newborn in her 1609 midwifery text. 2 She reported the case of a multiparous woman who delivered twins; one was hydropic and died soon after birth, and the other developed jaundice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Before treatment with plasma exchange treatment began a century ago, most infants with RhD alloimmunization died 7 . When immunization with Rho(D) immune globulin became available in 1968, severe hemolysis and hyperbilirubinemia in newborn infants became rare 8 . ABO alloimmunization may now be the most common cause neonatal hemolysis and hyperbilirubinemia, but it is rarely severe 9 .…”
Section: Clinical Feature Hereditary Ttp (4 Infants) Abo Incompatibil...mentioning
confidence: 99%
See 1 more Smart Citation
“…Before treatment with plasma exchange treatment began a century ago, most infants with RhD alloimmunization died 7 . When immunization with Rho(D) immune globulin became available in 1968, severe hemolysis and hyperbilirubinemia in newborn infants became rare 8 . ABO alloimmunization may now be the most common cause neonatal hemolysis and hyperbilirubinemia, but it is rarely severe 9 .…”
Section: Clinical Feature Hereditary Ttp (4 Infants) Abo Incompatibil...mentioning
confidence: 99%
“…7 When immunization with Rho(D) immune globulin became available in 1968, severe hemolysis and hyperbilirubinemia in newborn infants became rare. 8 ABO alloimmunization may now be the most common cause neonatal hemolysis and hyperbilirubinemia, but it is rarely severe. 9 When severe hemolysis with hyperbilirubinemia occurs soon after birth, it is often assumed that blood group alloimmunization is the cause.…”
mentioning
confidence: 99%
“…An outcome of this work was Fisher's masterly analysis of the genetics of the Rhesus blood group system (Fisher 1947), which brought order to a chaos of data. Incompatibility between the Rhesus make-up of the mother and foetus is a major cause of haemolytic disease of the newborn; understanding the genetics of Rhesus has enabled this disease to be largely prevented (Baskett 2019).…”
Section: Contributions To Geneticsmentioning
confidence: 99%
“…Rhesus D (Rh D) alloimmunization leading to hemolytic disease in the fetus and newborn, a preventable condition, carries a global burden of infirmity, resulting in some 50,000 fetal deaths annually, primarily in low and middle income countries in Asia and Sub-Saharan Africa [1]. In the developed world, however, the introduction of Rh immunoprophylaxis (RhIg) in the 1960s into routine obstetrical care for Rh negative women at risk lead to a dramatic fall in the number of Rh affected babies and is considered an immunological success story in the conquest of hemolytic disease of the fetus and newborn in these countries [2]. Initial clinical trials of postpartum administration of RhIg by Freda and Gorman in the US demonstrated that sensitization to the Rh-D antigen of Rh negative women delivering Rh positive newborns could be reduced more than tenfold from 14% to approximately 1% when susceptible women were administered RhIg after delivery of these offspring [3].…”
Section: Introductionmentioning
confidence: 99%